Integrasi dan Etika Artificial Intelligence dalam Pendidikan Agama Kristen: Kerangka Etis dan Implikasi Pedagogis di Era Digital - Novelia Pasaribu (STT Pelita Dunia, 2026)
This article reviews the relationship between Artificial Intelligence (AI) ethics and Christian Religious Education (CRE). The research problem addressed is how AI ethical principles can be applied in the context of Christian religious education, as well as the challenges and opportunities arising from this technological integration. The research methods used include literature review and qualitative analysis of relevant theological and technological sources. The aim of this research is to explore an ethical framework that can be utilized by Christian religious educators in addressing the advancements of AI, and to formulate practical guidelines that can be implemented in the Christian religious education curriculum. The novelty of this research lies in its interdisciplinary approach, combining technology ethics and Christian religious education, offering new insights into how these two fields can mutually support each other. The research findings indicate that applying AI ethics in Christian religious education is not only important for maintaining moral integrity in technology use, but also for enhancing teaching and learning effectiveness. This study identifies several key principles, such as justice, transparency, and responsibility, which should be foundational in the application of AI in religious education contexts. This research contributes significantly to the development of ethically responsible pedagogy in the digital era. Specifically, the findings show that CRE teachers need to develop faith-based digital literacy, Christian educational institutions need to design training curricula that embed the theological and ethical dimensions of AI use, and churches and faith communities need to provide a theological foundation for technology use in the education of younger generations. Practical recommendations from this study include the formulation of student data protection policies, the application of algorithmic fairness principles, and the strengthening of CRE teachers’ digital competence rooted in Christian values.